The General Practice and Residential Aged Care Facility Concordance of Medication (GRACEMED) study. (November 2020) - Makeham, Meredith; Pont, Lisa; Verdult, Carlijn; Hardie, Rae-Anne; Raban, Magdalena Z.; Mitchell, Rebecca; Purdy, Helen; Teichert, Martina; Ingersoll, Andrew; Westbrook, Johanna I.
Abstract: Background: The lack of interoperable IT systems between residential aged care facilities (RACF) and general practitioners (GP) in primary care settings in Australia introduces the potential for medication discrepancies and other medication errors. The aim of the GRACEMED study is to determine the extent and potential severity of medication discrepancies between general practice and RACFs, and identify factors associated with medication discrepancies. Methods: A cross sectional study of medication discrepancies between RACF medication orders and GP medication lists was conducted in the Sydney North Health Network, Australia. A random sample of RACF residents was included from practice lists provided by the general practices. RACF medication orders and GP medication lists for the included residents were compared, and medication discrepancies between the two sources were identified and characterised in terms of discrepancy type, potential for harm and associated factors. Results: 31 GPs and 203 residents were included in the study. A total of 1777 discrepancies were identified giving an overall discrepancy rate of 72.6 discrepancies for every 100 medications. Omissions were the most common discrepancy type (35.2%, ) followed by dose discrepancies (34.4%) and additions (30.4%). 48.5% of residents had a discrepancy with the potential to result in moderate harm and 9.8% had a discrepancy with the potential for severe harm. Number of medications prescribed was the only factor associated with medication discrepancies. Conclusion: Increased use of systems that allow information sharing and improved interoperability of clinical information is urgently needed to address medication safety issues experienced by RACF residents.